Considering subnational support of climate change policy in the United States and the implications of symbolic policy acts. Issue 6 (19th September 2022) - Hopper, JoyAnna S.; Swift, Clint S.
ABSTRACT: While existing literature points to a number of factors that shape subnational support for climate policy, the extant scholarship has struggled to illustrate a clear and convincing explanation for subnational support of climate policy efforts and whether that support is meaningful. By looking to the United States, where subnational actors have an important role in environmental policy development and implementation, we find that legislators' ideology and membership in the minority party determines sponsorship of climate bills. Specifically, liberal legislators with the fewest opportunities to signal efficacy to their constituents are the most likely to support subnational climate change policy efforts. Given that the individuals most likely to support climate policy efforts are those without capacity, many support efforts may be more symbolic than substantive.